1986
DOI: 10.1002/1097-0142(19860801)58:3<754::aid-cncr2820580324>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Malignant brenner tumor: A histologic, morphometrical, immunohistochemical, and ultrastructural study

Abstract: The histologic, morphometric, immunohistochemical, and ultrastructural study of a malignant Brenner tumor in a postmenopausal women presenting with vaginal bleeding is described. A comparison with transitional cell carcinomas is made, and the use of morphometry in grading the urothelial-like epithelium in malignant Brenner tumors is suggested. High preoperative urinary estrogen, low serum luteinizing hormone (LH) and follicle-stimulating hormone (FSH) levels and histologically confirmed atypical endometrial hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 19 publications
(3 reference statements)
2
23
0
1
Order By: Relevance
“…Benign Brenner tumour admixed with serous or mucinous carcinoma should not be diagnosed as Malignant Brenner tumour. Endometrial hyperplasia has been reported to coexist in 4-14% of women who have Brenner tumours [7] . Fox etalpresented cases of MBT with abnormal vaginal bleeding [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Benign Brenner tumour admixed with serous or mucinous carcinoma should not be diagnosed as Malignant Brenner tumour. Endometrial hyperplasia has been reported to coexist in 4-14% of women who have Brenner tumours [7] . Fox etalpresented cases of MBT with abnormal vaginal bleeding [8] .…”
Section: Discussionmentioning
confidence: 99%
“…2 Malignant Brenner tumors are differentiated from transitional cell carcinomas of the ovary by the occurrence of an identifiable benign Brenner tumor next to the area of histologically malignant epithelium in the former. 1 Brenner tumors are mainly asymptomatic, and may have incidental findings, particularly if small. Clinical symptoms of a pelvic mass, such as pain or a palpable mass may be seen in tumors with larger dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Routine gynecological follow up is adequate. 1,3 The clinical and histological differentiation is important, because proliferative Brenner tumors have quite a favorable prognosis and may be treated in the same manner as the benign, whereas malignant Brenner tumors have a more guarded prognosis and require further intervention. In our case and the previous illustrated series, all cases were of a benign variety of Brenner tumor and conservative treatment and follow up was sufficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malign Brenner tümörleri solid veya mural nodüller içeren kistler şeklinde olabilir ve genelde ayırt edici özellikleri yoktur (7). Brenner Tümörlerinin %4-14'de endometrial hiperplazinin eşlik ettiği gösterilmiştir (8). Olgumuzda hastada endometrial patoloji saptanmamıştır.…”
Section: Introductionunclassified